{4-Hydroxy-N0-[(2E,3Z)-4-oxido-4- phenylbut-3-en-2-ylidene]benzohydrazidato}dimethyltin(IV) - Fasihuddin B, Ahmad; Fraser, White; MA, Affan; Edward R. T., Tiekink; Norrihan B, Sam (International Union of Crystallography, 2011)
The SnIV atom in the title compound, [Sn(CH3)2- (C17H14N2O3)], is five-coordinated within a C2N2O donor set provided by the N,N,O-tridentate ligand and two methyl groups. The resultant coordination geometry is intermediate between trigonal-bipyramidal and square-pyramidal. In the crystal, supramolecular zigzag chains propagating along the caxis direction are mediated by O—HO hydrogen bonds, and weak C—H interactions consolidate the packing.